Thrackles, Superthrackles and the Hanani-Tutte Theorem - Dehkordi, Hooman; Farr, Graham (Journal of Graph Algorithms and Applications, 2024)
A thrackle is a drawing of a graph in which any two vertex-disjoint edges cross exactly once and incident edges do not cross. A graph that has a thrackle drawing is thracklable. In the past three decades, mathematicians investigated a number of variations of thrackles by relaxing or changing the required number of crossings on edges or restricting the placement of vertices on the surface (e.g., restricting to outerdrawings, in which vertices are restricted to a boundary curve of the surface). A graph is superthracklable if it can be drawn so that any two edges cross exactly once. We provide a simple proof for the following: a graph can be drawn on the plane so that every two edges cross an odd number of times if and only if it is superthracklable on the plane. A graph is outersuperthracklable if it has a drawing on a disc in which every vertex is on the boundary of the disc and every pair of edges cross exactly once. We introduce some natural generalisations of outersuperthracklable graphs and we show that these classes of graphs are equivalent. Lastly, using the Hanani-Tutte characterisation of planar graphs we show that for any surface $Σ$, there is a relationship between the class of graphs that are not embeddable on $Σ$ and the class of graphs that are not superthracklable with respect to $Σ$. More specifically, we show how to construct, from any forbidden minor $G$ for embeddability in $Σ$, two infinite families of graphs that are not superthracklable with respect to $Σ$. This sheds further light on the relationship between some of Archdeacon and Stor's forbidden configurations for superthrackles and Kuratowski's forbidden minors for planarity.